2023
DOI: 10.1101/2023.07.18.549544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Refined Phylochronology of the Second Plague Pandemic in Western Eurasia

Abstract: Although dozens of ancient Yersinia pestis genomes and a vast corpus of documentary data are available, the origin and spread of consecutive outbreaks of the Second Plague Pandemic in Europe (14th-18th c.) are still poorly understood. For the majority of ancient genomes, only radiocarbon dates spanning several decades are available, hampering an association with historically recorded plague outbreaks. Here, we present new genomic evidence of the Second Pandemic from 11 sites in England, Estonia, the Netherland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Indeed, in this situation, Ind-7 but not Ind-44 tested positive for the plague agent Y. pestis, in line with previously reported detection of Y. pestis aDNA in this site (5). Present report is therefore one more illustration of dual infection in the course of documented plague, after cases of co-infection with Y. pestis has been reported with Treponema pallidum complex in a post-medieval and 17 th individual (26,27); with Haemophilus influenzae serotype b in 540 to 550 CE individual (28); with Bartonella quintana in individuals buried in a 11th-15th site in France (29). Furthermore, nine cases of Streptococcus spp.-Y.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, in this situation, Ind-7 but not Ind-44 tested positive for the plague agent Y. pestis, in line with previously reported detection of Y. pestis aDNA in this site (5). Present report is therefore one more illustration of dual infection in the course of documented plague, after cases of co-infection with Y. pestis has been reported with Treponema pallidum complex in a post-medieval and 17 th individual (26,27); with Haemophilus influenzae serotype b in 540 to 550 CE individual (28); with Bartonella quintana in individuals buried in a 11th-15th site in France (29). Furthermore, nine cases of Streptococcus spp.-Y.…”
Section: Discussionsupporting
confidence: 90%
“…This might limit our power to detect changes after the Black Death. None of the individuals in the pre– or post–Black Death groups are among those tested positive for Yersinia pestis previously ( 10 , 35 , 36 ). Our analyses of genetic ancestry ( Figs.…”
Section: Resultsmentioning
confidence: 96%
“…Such signs may indicate an infectious disease, such as venereal syphilis. The aDNA analysis confirmed that the deceased was infected by Treponema pallidum and the individual died because of plague (Yersinia pestis; Keller et al 2023). In addition, skeletons with venereal syphilis have been identified among those buried in the burial grounds of the Russian garrison in Kazan churchyard and in the hospital cemetery of the navy and army garrison in the 18th-century Tallinn.…”
Section: E N E R E a L S Y P H I L I Smentioning
confidence: 89%